Melestarikan Kesenian Tari Piring Diateh Talua Ciri Khas Batu Bajanjang - Azmen Kahar; Nur Putri Khalbi; Hilda Nurhidayati; Ravel Dwi Septia Andika; Yudi Mubarok (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Traditional arts are an important part of cultural heritage that must be preserved. One of the unique and distinctive art forms from Batu Bajanjang, Lembang Jaya District, in Solok Regency, West Sumatra, is the Plate Dance in Ateh Talua. This dance has deep philosophical values and requires extraordinary skills from the dancers. However, modernization and the decreasing interest of the younger generation are major challenges in preserving this dance. This article discusses the History of Plate Dance Art, Plate Dance Art in Diateh Talua, and efforts that can be made to Preserve Plate Dance in Ateh Talua so that it remains part of the cultural identity of the Batu Bajanjang community. Through education, cultural festivals, and government and community support, this art can continue to develop and be passed on to future generations.